Leveraging Community-University Partnerships to Develop a Strength-Based and Individualized Approach to Humanizing Housing Service Delivery for Individuals with Fetal Alcohol Spectrum Disorder (FASD) - Pei, Jacqueline; Poth, Cheryl; Carlson, Elizabeth; Joly, Vannesa; Mattson, Danielle; Patricny, Nicol; Badry, Dorothy; Mugford, Richard; Mastrangelo, Tracy; McFarlane, Audrey (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2022)
This field report summarizes and advances key learnings for leveraging community–university partnerships addressing housing service gaps for high-risk, marginalized populations with complex needs. We describe our navigation of existing and forged intersections to develop a strength-based and individualized approach to humanizing housing service delivery for individuals with fetal alcohol spectrum disorder (FASD). Our account is framed by four questions: why community and university partners came together to develop a responsive approach through the CanFASD network; who became key stakeholders in the partnership; how our humanizing housing approach is guiding the navigation of complexities inherent in service delivery for individuals with FASD; and what insights about creating intersections are we applying to our community-university partnerships.